Development of a grinding model based on flotation performance. (1st June 2021) - Mathe, Enoque; Cruz, Constanza; Lucay, Freddy A.; Gálvez, Edelmira D.; Cisternas, Luis A.
Graphical abstract: Highlights: A grinding model is developed for preliminary studies in flotation circuits. The model uses fine-slow, medium-fast, and coarse-slow species. The grinding model is easy to integrate into flotation simulations. The model is applied to a copper sulfide mineral with acceptable results. The significant advantage of the modeling method is its simplicity and low cost. Abstract: Usually, the concentration of minerals is carried out with a set of flotation and grinding units. Most of the modeling strategies for the flotation and grinding stages have followed separate developmental paths. This paper presents a strategy based on using flotation studies to model flotation and grinding via an integrated approach. The methodology, which is an approximate method that allows one to study of the effects of grinding on flotation circuits, is applied to a copper sulfide mineral with appropriate results. Given its nature, the application of this method will help preliminary studies on the design, improvement, and simulation of flotation circuits. The major advantages of this method are its simplicity and low cost. Thus, the main contribution of this work is a new strategy to model grinding for integration into the modeling of flotation circuits. This new strategy can be extended to other concentration technologies that include grinding.